2000
DOI: 10.1007/s004250000332
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-acyl carrier protein thioesterase activity from sunflower ( Helianthus annuus L.) seeds

Abstract: During sunflower (Helianthus annuus L.) seed formation there was an active period of lipid biosynthesis between 12 and 28 days after flowering (DAF). The maximum in-vitro acyl-acyl carrier protein (ACP) thioesterase activities (EC 3.1.2.14) were found at 15 DAF, preceding the largest accumulation of lipid in the seed. Data from the apparent kinetic parameters, Vmax and Km, from seeds of 15 and 30 DAF, showed that changes in acyl-ACP thioesterase activity are not only quantitative, but also qualitative, since, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…This comparison demonstrated that the protein encoded by HaFatA1 is highly homologous to FatA thioesterases, and more specifically with those of the ''campanulids'' group like Carthamus tinctorius (Knutzon et al 1992) and Coriandrum sativum (Do¨rmann et al 1994). Significantly, HaFatA1 was clearly different from the FatB thioesterases, confirming the presence of a FatA type thioesterase in developing sunflower seeds as previously proposed by Martı´nez-Force et al (2000).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This comparison demonstrated that the protein encoded by HaFatA1 is highly homologous to FatA thioesterases, and more specifically with those of the ''campanulids'' group like Carthamus tinctorius (Knutzon et al 1992) and Coriandrum sativum (Do¨rmann et al 1994). Significantly, HaFatA1 was clearly different from the FatB thioesterases, confirming the presence of a FatA type thioesterase in developing sunflower seeds as previously proposed by Martı´nez-Force et al (2000).…”
Section: Resultssupporting
confidence: 85%
“…The soluble and membrane-bound protein fractions from E. coli cells expressing FatA1 thioesterase were collected and assayed for thioesterase activity using 18:1-ACP, the preferred substrate for sunflower FatA thioesterase (Martı´nez-Force et al 2000). The acyl-ACP thioesterase activity was approximately 20,000 fold higher in cells containing pQEFATA than in control cells.…”
Section: Expression Of Sunflower Fata1 Thioesterase In Escherichia Colimentioning
confidence: 99%
See 2 more Smart Citations
“…WoLF PSORT was used to identify the signal peptide and the cleavage site where the mature protein begins, a program that predicts protein subcellular localization (Horton et al, 2007), with the information available for acyl-ACP thioesterases from Arabidopsis thaliana (Dörmann et al, 1995), Helianthus annuus (Martínez-Force et., al, 2000;Serrano-Vega et al, 2005) Gossypium hirsutum (Huynh et al, 2002), Diploknema butyracea (Jha et al, 2006), Madhuca longifolia (Ghosh and Sen, 2007), Ricinus communis (Sánchez-García et al, 2010) and Macadamia tetraphylla (Moreno-Pérez et al, 2011). Val-55 was the best candidate to represent the N-terminal amino acid of the mature CsFatA protein, corresponding to a signal peptide of 58 amino acid residues (Fig.…”
Section: Isolation and Sequence Analysis Of Acyl-acp Thioesterases Frmentioning
confidence: 99%